(untitled) (Research, Society and Development, 2021)
Palliative Care are innovations in healthcare assistance and have stood out in Brazil in the last decade. This research aimed at understand the competences for professional practice in Palliative Care in the Adult Intensive Care Unit (ICU), through an descriptive and exploratory study, with a qualitative approach, performed at an ICU of a public hospital in Fortaleza, state of Ceara. Data was collected between July and August 2019, through a sociodemographic/professional questionnaire as well as semi-structured interviews. Participants were five (5) nurseries, twelve (12) physiotherapists, eight (8) physicians and eleven (11) nursing technicians. In data collection, Minayo´s thematic analysis was used. As a result, four categories arose: The palliative approach is recent; the team, patients and their families; the multidisciplinary team in palliation; and Palliative Care. It was noted that the participants, although were not trained in Palliative Care, had knowledge about them. Professional practice in the care of palliative patients was highlighted in the actions developed in the Adult ICU, with divergences in the speeches of the participants. Theoretical-practical knowledge and the engagement of the multiprofessional team were basic tools for the care of palliative patients; the communication failure in the multiprofessional team was recurrent.